2021
DOI: 10.5847/wjem.j.1920-8642.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophils and mortality in patients with acute respiratory distress syndrome: A propensity score matching analysis

Abstract: BACKGROUND: The effect of blood eosinophils (EOSs) on mortality in acute respiratory distress syndrome (ARDS) patients and whether corticosteroids aff ect this eff ect are unclear. METHODS: The Medical Information Mart for Intensive Care III database (version 1.4) was used to extract data. Patients with ARDS were selected for inclusion. Cox regression models using the backward stepwise method and propensity score matching (PSM) were used to assess the relationship between blood EOS counts and 28-day mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In present study, we found that patients with high level of baseline eosinophils (>0.3%) had significantly lower 30-day mortality than non-survivors in univariate and multivariate analyses, which is similar to previous studies. 13 , 24 The results from Kaplan–Meier curve and random forest model also supported the above findings. Of note, when we regarded blood eosinophils as a continuous variable, no significant association was found in the multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In present study, we found that patients with high level of baseline eosinophils (>0.3%) had significantly lower 30-day mortality than non-survivors in univariate and multivariate analyses, which is similar to previous studies. 13 , 24 The results from Kaplan–Meier curve and random forest model also supported the above findings. Of note, when we regarded blood eosinophils as a continuous variable, no significant association was found in the multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Up to date, there are only two published studies that have described the relationship between blood eosinophils and clinical outcomes in patients with ARDS. 11 , 13 Zhu et al 11 observed that following clinical treatment, patients with increased levels of blood eosinophils at discharge are associated with increased survival. Moreover, Chen et al 13 found that patients with higher baseline eosinophils had lower 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One main subject of research based on public intensive care databases was to analyze whether some factors affected the prognosis or mortality of critically ill patients. Researches focused on several common diseases such as acute respiratory distress syndrome, sepsis shock, acute renal failure, intracerebral hemorrhage and myocardial infarction [11][12][13][14][15] [22]. Jingjie Feng et al developed an improved continuous BP estimation method with more accuracy and less calibration frequency utilizing hemodynamic covariates in addition to pulse transit time [23].…”
Section: Abstract Analysismentioning
confidence: 99%